Impact of Climate Change on Dengue Hemorrhagic Fever (DHF) in Tropical Countries: A Literature Review - Shara Nuzila Ramadhani; Mohd. Talib Latif (Universitas Airlangga, 2021)
Introduction: Dengue Hemorrhagic Fever (DHF) is a zoonotic disease that is most wary because the cases reported by WHO increased quite drastically from 2.4 million cases to 5.2 million cases in 2010-2019 globally. In 2020, the DHF rate increased by 953,476, and the majority occurred in tropical countries. In response to this, WHO emphasized that climate and weather variables can play an important role in predicting the DHF outbreak. This article was written to find out the impact of climate change on the incidence of DHF. Discussion: The literature review method was used in writing this article by utilizing article searches in online databases, namely PubMed, DOAJ, Proquest, and Science Direct. Amount 11 articles related to the title have been selected as literacy materials. Climatic variables consisting of temperature, rainfall, and humidity have the potential to increase the incidence of DHF. Conclusion: It can be concluded that climate change indicators can affect the breeding place of the Aedes aegypty, making the various incidence of DHF cases in tropical or subtropical countries. This can be an early warning for each region always to carry out active surveillance in detecting the risk of increasing DHF cases in certain weather.